Ultrasound evaluation of clinical mimics of deep vein thrombosis: essential insights for radiologists in interpretation - Dongsuk Im; Lyo Min Kwon; Sun Young Park; Min Su Park; Won Ju Hong (Ultrasonography)
Ultrasonography (US) is a sensitive and radiation-free technique for diagnosing deep vein thrombosis (DVT). Therefore, when DVT is clinically suspected but not detected on US, radiologists should consider a range of alternative differential diagnoses. This review article presents the imaging findings of clinical conditions that mimic DVT, which can be distinguished using a multimodal radiologic approach. Additionally, DVT mimics can be categorized into two groups based on whether a flat or normal waveform is observed on Doppler US. This article details the imaging findings and clinical presentations of DVT mimics, organized by these classifications. This information may help radiologists make more accurate diagnoses, enabling patients to receive appropriate treatment in a timely manner.